Blocking and degradation of aflatoxins by cold plasma treatments: Applications and mechanisms. (March 2021) - Wu, Yue; Cheng, Jun-Hu; Sun, Da-Wen
Abstract: Background: Aflatoxins are one of the maximal menaces to food safety and public health and can contaminate food during the entire process from field to table, which can then be digested by the consumer, causing irreversible negative impacts such as immunotoxic, carcinogenic, and mutagenic effects. Therefore, development of novel technology to decontaminate aflatoxins is obviously important for the food industry. Cold plasma (CP) is an emerging novel nonthermal technology with eco-friendliness, high-efficiency and low cost, which has recently been widely studied for inactivating microorganisms and mycotoxins. Scope and approach: This review presents a brief overview of aflatoxins and cold plasma treatment (CPT) and provides detailed information on the blocking and degradation of aflatoxins by CPT and its potential mechanisms. Furthermore, the superiority of CPT in purifying aflatoxins is highlighted by comparison with conventional methods including physical, chemical and biological treatments. Finally, the limitations and challenges of CPT are also discussed. Key findings and conclusions: Recent studies show that CPT is an alternative technique to conventional methods for aflatoxins decontamination. However, the effective components and exact sites where CPT works are not completely clear, and the types of food researched are also few. Further researches should focus on breaking through these bottlenecks and provide a theoretical basis for the promotion of CPT applications. Highlights: Aflatoxins contamination is a vital challenge facing the food industry. Cold plasma treatment (CPT) shows great feasibility of decontamination. CPT has superiority in purifying aflatoxins compared with traditional methods. The potential mechanism of aflatoxins decontamination is discussed.